Hubungan Visceral Adiposity Index dengan Neuropati Diabetik Perifer pada Pasien Diabetes Melitus Tipe 2 - Sanusi, Muhammad Arif; Lubis, Dian Anindita; Syafril, Santi (Jurnal Penyakit Dalam Indonesia, 2025)
Introduction. Type 2 diabetes mellitus (T2DM) is the leading metabolic disease in Indonesia. Diabetic peripheral neuropathy (DPN), a major complication of T2DM, was associated with insulin resistance and adipose dysfunction. Visceral adiposity index (VAI) is a tool to measure visceral fat as the indicator of adipose dysfunction and insulin sensitivity. The association between VAI and DPN has not been widely researched, especially in Indonesia. This study aims to assess the association between them. Methods. This was a cross-sectional study conducted on adult patients (aged ≥18 years) with T2DM at H. Adam Malik General Hospital, Medan, from December 2024 to March 2025. DPN was assessed using the Michigan Neuropathy Screening Instrument (MNSI), consisting of a questionnaire (MNSI A) and physical examination (MNSI B). VAI was calculated using waist circumference, body mass index (BMI), triglyceride level, and high-density lipoprotein (HDL) cholesterol level. A bivariate analysis was conducted to compare mean VAI values between patients with and without DPN and to assess correlations between VAI and MNSI scores. Results. From a total of 80 subjects, the average age was 56 years (SD 9), and the majority were female (56.3%). The median VAI value in the DPN group was 2.863 (0.401–11.665), slightly higher than in the non-DPN group, which was 2.549 (0.781–17.414), but the difference was not statistically significant (p=0.34). No statistically significant correlation was found between VAI and MNSI A score (r=0.092; p=0.42) or MNSI B score (r=0.12; p=0.31). Conclusion. There was no significant association between VAI and DPN in patients with T2DM.